DIGITAL COMMUNICATION'S ROLE IN SHAPING INDONESIAN THRIFT CULTURE: A LITERATURE REVIEW - Tsaqif Kusindriyanti , Nourmalihah; Utari, Prahastiwi; Sudarmo, Sudarmo (LPPM Universitas Duta Bangsa Surakarta, 2023)
Thrifting is defined as the consumption of used branded fashion products at a lower price, which is often associated with a person's lifestyle and identity. The purpose of this research is to find out how the role of digital marketing communication and creative content on thrifting goods to attract young people in Indonesia. This research is a qualitative research using literature review method. The results of this study show that the utilization of digital communication in thrifting marketing is done with two media. The use of Instagram as a digital communication tool is done by: (1) uploading product information, (2) means of interactive communication with consumers, (3) use of hashtag features, and (4) marketing communication. The use of e-commerce as a digital communication tool includes: (1) eWOM and (2) live streaming. The existence of social media and e-commerce has a significant impact in increasing awareness and motivation to thrift. Innovative and creative use of digital materials is needed to strengthen brand identity and increase consumer awareness, which in turn will increase sales.